2020
DOI: 10.1590/1519-6984.192643
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative activity of essential oils from three plants of the Brazilian Cerrado: Campomanesia adamantium (Myrtaceae), Protium ovatum (Burseraceae) and Cardiopetalum calophyllum (Annonaceae)

Abstract: Abstract Essential oils, which may be extracted from several parts of plants, have different biological activities. The Brazilian Cerrado has a large variety of plants that yield essential oils, even though many have not been studied yet. Taking into account the biodiversity of this biome, this study aimed at evaluating the antiproliferative activity of essential oils extracted from three species of plants of the Cerrado in Goiás state: Campomanesia adamantium (Cambess.) O. Berg, Protium ovatum (Engl.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…The antiproliferative activity of the EO from Cardiopetalum calophyllum leaves, which is mainly made up of spathulenol (28.78%), viridiflorol (9.99%), and (Z,E)-farnesol (6.51%), was evaluated in different human tumor cell lines: adenocarcinoma of the breast (MCF-7), cervical adenocarcinoma (HeLa), and glioblastoma (M059J), in addition to a normal human cell line (GM07492A, pulmonary fibroblasts). The IC 50 values ranged from 216.8 to 353.51 µg•mL −1 and selectivity was not observed [82].…”
Section: Antiproliferative and Cytotoxic Activitiesmentioning
confidence: 96%
“…The antiproliferative activity of the EO from Cardiopetalum calophyllum leaves, which is mainly made up of spathulenol (28.78%), viridiflorol (9.99%), and (Z,E)-farnesol (6.51%), was evaluated in different human tumor cell lines: adenocarcinoma of the breast (MCF-7), cervical adenocarcinoma (HeLa), and glioblastoma (M059J), in addition to a normal human cell line (GM07492A, pulmonary fibroblasts). The IC 50 values ranged from 216.8 to 353.51 µg•mL −1 and selectivity was not observed [82].…”
Section: Antiproliferative and Cytotoxic Activitiesmentioning
confidence: 96%
“…The compound is highly effective against the larvae of the mosquito species Anopheles subpictus, Aedes albopictus, and Culex tritaeniorhynchus, as well as having antioxidant activity and cytotoxic activity against melanoma cells [36,37]. The antibiotic [37] and antiproliferative activity [38] of Germacrene B has also been reported in the literature.…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 90%
“…Other studies have identified the in vitro antiproliferative activity of the extract from leaves of C. adamantium in many cell lineages, including murine melanoma cells (B16-F10) [143], prostate cancer cells (PC-3) [144], breast adenocarcinoma cells (MCF-7), cervical adenocarcinoma cells (HeLa), and glioblastoma cells (M059J) [145]. However, none of these studies evaluated the cell death profile induced by extract of C. adamantium .…”
Section: Cell Death Profile Induced By Plants From the Cerradomentioning
confidence: 99%